3D Vertically Aligned CNT/Graphene Hybrids from Layer‐by‐Layer Transfer for Supercapacitors. (25th July 2017) - Nagelli, Enoch A.; Huang, Liang; Dai, Alvin Q.‐Z.; Du, Feng; Dai, Liming
Abstract : The exceptional electrical, optical, thermal and mechanical properties make graphene and carbon nanotubes (CNTs) promising for a large variety of applications, including energy storage. In practice, it is higly important to translator these properties associated with the low‐dimensional carbon nanomaterials into bulk materials/devices. Recent theoretical studies have proven that three‐dimensional (3D) pillared architectures, consisting of parallel graphene layers intercalated by vertically aligned carbon nanotubes (VA‐CNTs) in between, possess desriable transport and mechanical properties in all dimensions while maintaining the excellent properties of their building blocks. However, it remains challenging to experimentally realize such 3D pillared graphene/VA‐CNT hybrids. Here, tunable 3D pillared graphene/VA‐CNT architectures are formed by chemical vapor deposition, and a template‐free contact transfer process is presented, involving the hydrophobic‐hydrophobic interactions between graphene and VA‐CNTs. The resultant 3D graphene/VA‐CNT hybrids are demonstrated to be efficient electrode materials for supercapacitors with good performance. This newly‐developed methodology holds great potential for fabricating various 3D architectures with many other materials for a wide range of multifunctional applications, including energy storage, electrical and thermal managements, and flexible electronics. Abstract : 3D pillared graphene/vertically aligned carbon nanotube (VA‐CNT) architectures are constructed by a facile yet versatile layer‐by‐layer transfer technique. Supercapacitors based on the newly developed graphene/VA‐CNT hybrid electrode show promising performance.